2020
DOI: 10.1111/fwb.13483
|View full text |Cite
|
Sign up to set email alerts
|

Future climate change will severely reduce habitat suitability of the Critically Endangered Chinese giant salamander

Abstract: Being the largest extant amphibian in the world, the IUCN Critically Endangered Chinese giant salamander Andrias davidianus is a charismatic species with great international public interest. While threats such as commercial overexploitation and habitat degradation have been extensively documented to affect natural populations of A. davidianus, still no information is available about the species sensitivity to climate change. Here, we develop an ensemble of species distribution models (SDMs) for A. davidianus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…Addressing the validity of the fitness-centre hypothesis has important implications for conservation and applied biodiversity management. Indeed, several conservation studies are based upon estimations of coarse modeled habitat suitability based on occurrence records to predict areas where species will most likely harbors individuals of that species (Peterson et al 2002, Fitzpatrick et al 2008, Zhang et al 2020). However, a lack of the underlying fitness-centre relationship alters our interpretation of how modeled probability of occurrence is linked to the ability of specimens to survive and grow in a given location, affecting decisions on where to prioritize conservation efforts.…”
Section: General Implicationsmentioning
confidence: 99%
“…Addressing the validity of the fitness-centre hypothesis has important implications for conservation and applied biodiversity management. Indeed, several conservation studies are based upon estimations of coarse modeled habitat suitability based on occurrence records to predict areas where species will most likely harbors individuals of that species (Peterson et al 2002, Fitzpatrick et al 2008, Zhang et al 2020). However, a lack of the underlying fitness-centre relationship alters our interpretation of how modeled probability of occurrence is linked to the ability of specimens to survive and grow in a given location, affecting decisions on where to prioritize conservation efforts.…”
Section: General Implicationsmentioning
confidence: 99%
“…Species distribution models (hereinafter SDMs) have been globally recognized as a useful tool in nature conservation and management, for instance, to refine the threat status of a species [61][62][63][64]. When applied to distribution data, they can predict distributions across geographic landscapes by multiple responses, improve image analysis or remote-sensing in order to lead the search for poorly known species [65][66][67][68], thus providing perceptions into the species' habitat, range and abundance [69][70][71][72][73].…”
Section: Species Distribution Modelsmentioning
confidence: 99%
“…For instance, Zhang, Mammola, Liang, et al. (2020) developed a SDM for the Critically Endangered Chinese giant salamander Andrias davidianus (Blanchard, 1871)—the world's largest extant amphibian—and found that this species might be extremely vulnerable to climate change and might lose more than two‐thirds of its suitable habitat in the future.…”
Section: Introductionmentioning
confidence: 99%